Unraveling the cognitive pathway: how critical thinking mediates the impact of anxiety and self-efficacy on informatics achievement in early adolescence - Muhammad Alwan Nursuhaida; I Nyoman Jampel; Komang Setemen; I Gusti Ngurah Pujawan; Gst. Ayu Mahayukti (Indonesian Institute for Counseling, Education and Therapy (IICET), 2025)
Informatics education in early adolescence demands high-order cognitive skills, yet student performance is frequently impeded by psychological barriers such as anxiety and low self-efficacy. While the direct effects of these factors are known, the specific cognitive mechanisms through which they influence academic achievement remain underexplored. This study investigates the structural pathways connecting anxiety and self-efficacy to informatics learning outcomes, specifically examining the mediating role of critical thinking skills. A predictive correlational design was employed involving 109 seventh-grade students. Data were collected using validated psychological scales and cognitive tests, then analyzed using path analysis to test the mediation hypothesis. The findings demonstrate that anxiety does not merely correlate with lower grades but significantly degrades critical thinking capabilities (cognitive interference). Conversely, self-efficacy acts as a predictor for the activation of these skills (cognitive facilitation). Crucially, critical thinking skills were found to significantly mediate the impact of both psychological factors on learning outcomes. These results suggest that emotional states influence informatics achievement primarily by modulating a student's capacity for algorithmic reasoning. Consequently, effective pedagogy must integrate psychological scaffolding to preserve the cognitive resources required for complex problem-solving.